Problematyka konstrukcyjna nowożytnych retabulów na przykładzie analizy wybranych ołtarzy z kościołów toruńskich - Kofel, Weronika (TECHNE. Seria Nowa, 2018)
The purpose of the article is to present the research methods and structural issues related to the modern-period retabula, illustrated with an example of selected Toruń-based altars in the Cathedral of St. John the Baptist and St. John the Evangelist, the Church of St. James the Greater, and the Church of the Assumption of the BVM. The article has been divided into four sections. The first one describes the research method applied to study the structure of modern-period retabula, which is a three-stage process including: the inventory of the building, aimed at drafting a measurement and drawing documentation, the production ofexploded-view drawings that contain details of structural solutions, and the description of the construction of the building, which also takes a three-stage form. In the next section, basic terms related to the construction of retabula have been presented, with distinguished structural types of retabula, divided into three catego: type S, S+ and SP. The issue of the dead load of wooden constructions and its distribution was also discussed, and the analysis of such properties rendered it possible to distinguish load-bearing, self-supporting and quasi-self-supporting structures among modern-period retabula. In addition, the issue of the structural layout of retabula and their modular design was discussed, with a description of the following modular units: simple, complex, mixed and combined modules. In the next part of the article, the current status of the research devoted to Toruń-based altars was presented, including a review of the most prominent publications on historical, stylistic and maintenance matters, with a particular focus on theworks by Piotr Trybuszewski and Peter Machala, related to structural issues of retabula. The final section of the article was devoted to the analysis of the structure of selected retabulain Toruń-based churches. A detailed structural study was conducted on the Altar of the Immaculate Conception of the Blessed Virgin Mary within the Cathedral of St. John the Baptist and St. John the Evangelist, and the Altar of St. Joseph in the Church of St. James the Greater. In this part, individual structural solutions were described, together with their construction and design types of their retabula. Next, the number of structural modules and their types were discussed, together with a presentation of a detailed design and structure of the modules, including the applied types of woodworking joints and connections.